4
$\begingroup$

How to prove $\dfrac{\sqrt\pi z^v}{2^v~\Gamma\left(v+\dfrac{1}{2}\right)}\int_0^\infty e^{-z\cosh t}\sinh^{2v}t~dt=\int_0^\infty e^{-z\cosh t}\cosh vt~dt$ ?

Does some formulae in http://dlmf.nist.gov/5.12 helpful?

$\endgroup$
2
$\begingroup$

Let $K_{\nu}(z)$ the modified Bessel function of the second kind (or Macdonald function). The function $K_{\nu}(z)$ admits the Sommerfeld integral representation $$ K_{\nu}(z)=\int_0^{\infty}\operatorname{e}^{-z\cosh t}\cosh(\nu t)\operatorname{d}t $$ for $|\arg z|<\frac{\pi}{2}$ and $\nu\in\Bbb C$.

If we take $\operatorname{e}^{-u}=t$, then $$ K_{\nu}(z)=\int_0^{\infty}\operatorname{e}^{-z\cosh t}\cosh(\nu t)\operatorname{d}t=\frac{1}{2}\int_0^{\infty}\operatorname{e}^{-\frac{z}{2}\left(u+\frac{1}{u}\right)}u^{-\nu-1}\operatorname{d}u $$ that can also be written as $$ K_{\nu}(2\sqrt{z\lambda})=\frac{1}{2}\left(\frac{\lambda}{z}\right)^{\nu/2}\int_0^{\infty}\operatorname{e}^{-zt-\frac{\lambda}{t}}t^{-\nu-1}\operatorname{d}t $$ Using the simple result $$ u^{-\nu-\frac{1}{2}}=\frac{1}{\Gamma\left(\nu+\frac{1}{2}\right)}\int_0^{\infty}\operatorname{e}^{-ux}x^{\nu-\frac{1}{2}}\operatorname{d}x \qquad \text{for}\;\frak{Re}(\nu)>-\frac{1}{2} $$ the integral becomes $$ K_{\nu}(z)=\frac{1}{2\Gamma\left(\nu+\frac{1}{2}\right)}\int_0^{\infty}x^{\nu-\frac{1}{2}}\left[ \int_0^{\infty}\operatorname{e}^{-u\left(x+\frac{z}{2}\right)-\frac{z/2}{u}}u^{-\frac{1}{2}}\operatorname{d}u \right]\operatorname{d}x $$ where the order of integration may be interchanged. The inner integral is a special case of $K_{\nu}$ for $\nu=-1/2$ and observing that $K_{1/2}(x)=K_{-1/2}(x)=\sqrt{\frac{\pi}{2x}}\operatorname{e}^{-x}$ (see http://dlmf.nist.gov/10.39#2), the integral is $$ K_{1/2}(2\sqrt{y\lambda})=\sqrt{\frac{\pi/2}{2\sqrt{y\lambda}}}\operatorname{e}^{-2\sqrt{y\lambda}} $$ with $y=\frac{z}{2}$ and $\lambda=x+\frac{z}{2}$, that is $$ K_{1/2}\left(2\sqrt{\frac{z}{2}\left(x+\frac{z}{2}\right)}\right)=\frac{1}{2} \left(\frac{z/2}{x+z/2}\right)^{-1/4} \sqrt{\frac{\pi}{x+z/2}}\operatorname{exp}\left(-2\sqrt{\frac{z}{2}\left(x+\frac{z}{2}\right)}\right) $$ With the substitution $\theta=\sqrt{\frac{x+z/2}{z/2}}$ in the remaining integral in $x$, one has $$ K_{\nu}(z)=\frac{\sqrt\pi (z/2)^{\nu}}{\Gamma\left(\nu+\frac{1}{2}\right)}\int_1^{\infty} \operatorname{e}^{-z\theta}(\theta^2-1)^{\nu-\frac{1}{2}}\operatorname{d}\theta $$ The change of variables $\theta=\cosh t$ yields $$ K_{\nu}(z)=\frac{\sqrt\pi (z/2)^{\nu}}{\Gamma\left(\nu+\frac{1}{2}\right)}\int_0^{\infty} \operatorname{e}^{-z\cosh t}\sinh^{2\nu}t\operatorname{d}t. $$ This ends the proof.

$\endgroup$
  • $\begingroup$ Thank you very much! But if you can think the procedure that can without need to change the integrand to the algebraic form first this should be better. $\endgroup$ – Harry Peter Nov 9 '13 at 4:06
  • $\begingroup$ Can the similar approach applicable to the integral like math.stackexchange.com/questions/510127? $\endgroup$ – Harry Peter Nov 9 '13 at 4:09

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.